Dynamics of Learning Autonomy in Economics Learning: A Bibliometric Exploration - Sadiah, Emas; Purnamasari, Imas (Universitas Muhammadiyah Surakarta, 2025)
This study aims to map the development of learning autonomy research in economic learning through bibliometric analysis of Scopus-indexed publications for 2005–2025. The method used is bibliometric, with the stages of identification, selection, and document analysis using the Biblioshiny R application. From 17,104 initial publications, 30 selected relevant documents were analyzed in depth. The novelty of this study lies in the systematic mapping of trends, collaboration patterns, and thematic dynamics of learning autonomy research that has not previously been explored quantitatively in economics. The main findings show an annual publication growth of 5.65%, with dominant contributions from authors and institutions in China, especially Hunan University and author Chen L. The primary focus of the research remains on the issues of